ANALISIS STRATEGI INTEGRATED MARKETING COMMUNICATION TERHADAP MINAT MAHASISWA PENDIDIKAN EKONOMI UNIVERSITAS MUHAMMADIYAH METRO - Triani Ratnawuri; Meyta Pritandhari; Elmira Febri Damayanti (PROMOSI: Jurnal Program Studi Pendidikan Ekonomi, 2020)
Integrated Marketing Communication (IMC) Strategies include Advertising, Sales Promotion, Events and Experience, Public Relations and Publicity, Direct Marketing, Interactive Marketing, Word of mouth Marketing, Personal Sales. Implementation of Integrated Marketing Communication (IMC) strategy at Muhammadiyah Metro University has been applied all. Recapitulation of interview result with student in choosing campus and study program of economics at Muhammadiyah Metro University can be seen that student interest for college campus Muhammadiyah Metro University obtained by students that is 32 or 64% come from relatives (family, alumni, relatives) who have experience from the University of Muhammadiyah Metro especially alumni who has provided information to his relatives to enter the University of Muhammadiyah Metro Prodi Economic Education. Students' interest in choosing the study program and the campus is influenced by relatives (alumni, relatives, friends, family) who have had experience in the campus of Muhammadiyah Metro University. Giving information coming from relatives into the Word of Mouth strategy can be a mainstay because it is effective in persuading and influencing decisions from prospective students.Keywords: Integrated Marketing Communication, Interests, Marketing Strategy